The buried bones mystery - Draper, Sharon M. (Sharon Mills); Watson, Jesse Joshua (New York Aladdin, 2011)
After the neighborhood basketball court is vandalized, Ziggy and his friends decide to form a club called the Black Dinosaurs and build their clubhouse in Ziggy's backyard.
M
"Originally published as the series title 'Ziggy and the Black Dinosaurs"'--T.p. verso.
700
M
Keywords: Clubs -- Fiction; African Americans -- Fiction; Mystery and detective stories